Design and synthesis of a novel spinnable polyborazine precursor with high ceramic yield via one‐pot copolymerization. Issue 11 (5th July 2021) - Du, Yiang; Wang, Bing; Li, Wei; Song, Quzhi; Shao, Changwei; Han, Cheng; Wang, Yingde
Abstract: Synthesis of spinnable precursors with high ceramic yield is a crucial issue in BN fibers manufacturing by polymer‐derived ceramics (PDCs) route. Spinnability and high ceramic yield are the basis of precursor processability, formability, and mechanical properties. Herein, based on DFT simulation, we designed and synthesized a novel polymer precursor poly[2‐propylamino‐4, 6‐bis(methylamino) borazine‐co‐tri(methylamino) borazine] (PPMAB) via a facile one‐pot copolymerization strategy. The random copolymerization model of condensations was obtained through DFT calculation. The molecular chain structure, molecular weight, and molecular weight distribution were optimized by adjusting the synthesis conditions. The precursor PPMAB‐1:1 with a high ceramic yield of 62.43% and concentrated molecular weight distribution (PDI < 1.3) was obtained. Rheological performance research revealed the excellent and stable spinnability of PPMAB‐1:1 by the tunable viscosity and low flow activation energy (23.61 kJ/mol). As a demonstration of spinnability, continuous BN fiber with a fine diameter (>10 km, 7.60 ± 1.13 μm, and 1.6 GPa) was obtained after melt spinning. The present work effectively improved the ceramic yield and spinnability of polyborazine precursors. Simultaneously, it can be used extensively as a universal method to prepare multifunctional copolymers with precise structure control. Abstract : A novel BN precursor with excellent spinnability and high ceramic yield was designed and synthesized by one‐pot copolymerization based on DFT calculation. The molecular composition and linear chain structure were optimized to achieve continuous spinning and strength improvement.